Abnormal Site Preference of Al and Ga in Gd3Al2.3Ga2.7O12:Ce Crystals. Issue 8 (26th May 2021) - Li, Mingqing; Meng, Meng; Chen, Jie; Sun, Yiyang; Cheng, Guofeng; Chen, Lu; Zhao, Shuwen; Wan, Bo; Feng, He; Ren, Guohao; Ding, Dongzhou
Abstract : Large‐sized Gd3 Al2.3 Ga2.7 O12 :Ce single crystals are grown by the Czochralski method. The distribution of Al and Ga at octahedral (oct‐, 6‐oxygen‐coordinated) and tetrahedral (tet‐, 4‐oxygen‐coordinated) sites in the crystal is studied. Rietveld refinement is used to analyze the site occupation of Al and Ga. The results show that Ga ions with a larger radius than Al ions prefer to occupy the more compact tetrahedral sites. Density functional theory calculations show that the energy for a Ga ion at the tetrahedral site is lower than that at the octahedral site in the Gd3 Al5 O12 crystal, whereas the case for Al occupation in the Gd3 Ga5 O12 crystal is opposite. Slater rules are used to estimate the effective charge number of different ions, and the distribution of coordination ions around the octahedral and tetrahedral sites is analyzed. Then, the interaction between ions is simplified and the repulsive energy between Al/Ga and the coordination ions is calculated, which could provide reasonable understanding on the abnormal occupation. In addition, the occupation of Sc in Gd/Y garnet systems is also discussed using this method. Abstract : According to Rietveld refinement and density functional theory calculations, herein it is found that Ga ions with a larger radius than Al ions prefer to occupy the more compact tetrahedral sites in Gd3 Al2 Ga3 O12 crystals. A reasonable explanation for this abnormal occupation could be provided by analyzing the effective charge of ions and the distribution of coordination ions.